MATHEMATICAL CRITICAL THINKING ABILITY REVIEWED FROM SELF-EFFICACY IN DISCOVERY LEARNING - Ghina Nafs Nugroho; Onwardono Rit Riyanto (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
Critical thinking skills are needed as competitive capital in the future. Critical thinking ability is the most important goal taught in mathematics learning. One of the supporting factors for students' success in mathematical critical thinking is the level of self-efficacy. This study aims to determine whether there is an increase in mathematical critical thinking skills in terms of self-efficacy in discovery learning learning. The research design used is mastered experiments using quantitative data. The population of this study was class VII Cirebon 8 Public Middle School and the sample taken was class VII B. The results showed that (1) self-efficacy students'had an average of 78.14 which was quite good. (2) Mathematical critical thinking skills of students have increased based on the results of pre-tests and p-test. (3) There is an increase in students 'critical thinking skills after learning which is viewed from self-efficacy students'.Keywords: Mathematical critical thinking ability, self-efficacy